Gene Expression Profile of Mycobacterium leprae Contribution in the Pathology of Leprosy Neuropathy - Souza, Beatriz Junqueira de; Mendes, Mayara Abud; Sperandio da Silva, Gilberto Marcelo; Sammarco-Rosa, Patrícia; Moraes, Milton Ozorio de; Jardim, Marcia Rodrigues; Sarno, Euzenir Nunes; Pinheiro, Roberto Olmo; Mietto, Bruno Siqueira (Frontiers in Medicine, 2022)
Peripheral neuropathy is the main cause of physical disability in leprosy patients. Importantly, the extension and pattern of peripheral damage has been linked to how the host cell will respond against Mycobacterium leprae (M. leprae) infection, in particular, how the pathogen will establish infection in Schwann cells. Interestingly, viable and dead M. leprae have been linked to neuropathology of leprosy by distinct mechanisms. While viable M. leprae promotes transcriptional modifications that allow the bacteria to survive through the use of the host cell's internal machinery and the subvert of host metabolites, components of the dead bacteria are associated with the generation of a harmful nerve microenvironment. Therefore, understanding the pathognomonic characteristics mediated by viable and dead M. leprae are essential for elucidating leprosy disease and its associated reactional episodes. Moreover, the impact of the viable and dead bacteria in Schwann cells is largely unknown and their gene signature profiling has, as yet, been poorly explored. In this study, we analyzed the early differences in the expression profile of genes involved in peripheral neuropathy, dedifferentiation and plasticity, neural regeneration, and inflammation in human Schwann cells challenged with viable and dead M. leprae. We substantiated our findings by analyzing this genetic profiling in human nerve biopsies of leprosy and non-leprosy patients, with accompanied histopathological analysis. We observed that viable and dead bacteria distinctly modulate Schwann cell genes, with emphasis to viable bacilli upregulating transcripts related to glial cell plasticity, dedifferentiation and anti-inflammatory profile, while dead bacteria affected genes involved in neuropathy and pro-inflammatory response. In addition, dead bacteria also upregulated genes associated with nerve support, which expression profile was similar to those obtained from leprosy nerve biopsies. These findings suggest that early exposure to viable and dead bacteria may provoke Schwann cells to behave differentially, with far-reaching implications for the ongoing neuropathy seen in leprosy patients, where a mixture of active and non-active bacteria are found in the nerve microenvironment.